THE IMPACT OF ACCOUNTING IMPLEMENTATION, BUDGET USER BEHAVIOR, AND INTERNAL CONTROL ON FRAUD PREVENTION OF REGIONAL APPARATUS ORGANIZATIONS IN ARU ISLANDS REGENCY - Warkula, Yohanes Zefnath; Kusumawati, Dr. Andi; Nirwana, Dr. Nirwana (jfpublisher, 2022)
Good accounting implementation by government and optimal supervision toward the quality of government financial reports are expected to improve the accountability of government agencies' performance. Therefore, the performance of governmental administration can be optimal. This study aims to empirically test the application of accounting, budget user behavior, and internal control that affect the prevention of fraud in Government of Aru Islands Regency. This research used quantitative research with descriptive approach, it use Slovin sample formula, and the sample needed by the author to process data is 148 people from 236 specified populations. Based on the the results and discussion of the research, it can be concluded several things that: Partial internal control has significant positive effect on fraud prevention in Aru Islands Regency Government.